Optimizing the Return to Sport (RTS) Process Following Anterior Cruciate Ligament Reconstruction (ACLR) - Wołek, Filip; Browarska, Emilia; Miemczyk, Katarzyna; Mszyca, Igor; Michalski, Łukasz; Gajewska, Nicole; Mularczyk, Karolina Natalia; Kucharski, Kacper; Aksamit, Anna; Superson , Katarzyna; Maciak, Martyna (Quality in Sport, 2026)
Introduction: Return to sports (RTS) following anterior cruciate ligament reconstruction (ACLR) is a critical and multifaceted stage of rehabilitation. The traditional approach, based on rigid time frames (6–9 months), is increasingly giving way to modern, individualized, criteria-based protocols. The aim of this study is to synthesize the current literature (2021–2026) on optimizing the decision-making process for RTS after ACLR. Materials and Methods: A review of the scientific literature from the PubMed, Scopus, and Web of Science databases for the years 2021–2026 was conducted. Studies evaluating the effectiveness of biological criteria, symmetry indices, functional tests, and patients’ psychological readiness were analyzed. Results: The analysis showed that the process of graft ligamentization often takes more than 2 years, which calls into question the safety of early RTS based solely on the time criterion. The commonly used limb symmetry index (LSI ≥ 90%) has low predictive value and may mask bilateral muscle strength deficits caused by arthrogenic inhibition (AMI). Standard horizontal jump tests have proven insufficient; it is essential to incorporate vertical and lateral jump tests, as well as three-dimensional biomechanical analysis of movement. Psychological readiness (measured by the ACL-RSI scale) and the level of kinesiophobia are key determinants of success, showing a strong correlation with the risk of re-injury. In rotational sports, on-field rehabilitation based on reactive agility is crucial. Conclusions: A safe return to sport (RTS) after ACLR requires moving away from time-based criteria in favor of multidimensional algorithms based on objective biomechanical, functional, and psychological tests. The decision to return to competition should be a continuous process carried out by an interdisciplinary team of specialists to minimize the risk of secondary injury.